Intervenção em comportamento autolesivo em estudantes adolescentes sobralenses: um delineamento cooparticipativo entre membros da comunidade escolar - Silva, Jânder Carlos Soares (2025)
Adolescence is characterized as a phase permeated by biopsychosocial conflicts, and an increase in self-harm behavior has been increasingly observed in this age group. School, an institution that welcomes these adolescents for pedagogical purposes, is also the place where self-harm will be most easily perceived and identified. The objective of this study was to develop a shared intervention design with the school community, in the face of selfharm in this educational environment, together with the public school system of Sobral, with elementary school students from a full-time school, with a view to discussing and formulating public policies that satisfactorily meet this demand. To this end, this study will be presented in two sections: the first being theoretical, based on a systematic review to analyze interventions already discussed in the literature. The second section is empirical, where active listening and training workshops were held with students, teachers and other members of the school community. There are still difficulties in working on the topic of self-harm, especially due to complaints of lack of knowledge on the topic, as well as the need to structure preventive and intervention management strategies, focusing on the development of identification and care skills among the school community. Effective strategies include professional training, formation of student peers, creation of a reference team for support within the school, training in emotional regulation skills included in subjects of the school curriculum, as well as direct work with families. It is concluded that even in the face of the obvious demand for self-harm in the school environment, this topic still raises more effective public policies to address it.